2022
DOI: 10.3390/polym14112241
|View full text |Cite
|
Sign up to set email alerts
|

Plastic/Natural Fiber Composite Based on Recycled Expanded Polystyrene Foam Waste

Abstract: A novel reinforced recycled expanded polystyrene (r-EPS) foam/natural fiber composite was successfully developed. EPS was recycled by means of the dissolution method using an accessible commercial mixed organic solvent, while natural fibers, i.e., coconut husk fiber (coir) and banana stem fiber (BSF) were used as reinforcement materials. The treatment of natural fibers with 5% (w/v) sodium hydroxide solution reduces the number of –OH groups and non-cellulose components in the fibers, more so with longer treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…They further revealed that the alkaline treatment of coconut shells helped to improve the mechanical properties of the WPC. Furthermore, Sriprom, Sirivallop [80] used coconut husk fibre and banana stem fibre reinforcements to produce wood-plastic composites based on recycled expanded polystyrene waste. Their results affirm that treating fibre with sodium hydroxide increased the adhesion of fibres to the matrix.…”
Section: Expanded Polystyrene In Wood Plastic Compositesmentioning
confidence: 99%
“…They further revealed that the alkaline treatment of coconut shells helped to improve the mechanical properties of the WPC. Furthermore, Sriprom, Sirivallop [80] used coconut husk fibre and banana stem fibre reinforcements to produce wood-plastic composites based on recycled expanded polystyrene waste. Their results affirm that treating fibre with sodium hydroxide increased the adhesion of fibres to the matrix.…”
Section: Expanded Polystyrene In Wood Plastic Compositesmentioning
confidence: 99%
“… Eight articles described different materials and processes with environmentally friendly attributes. Sriprom and collaborators [ 12 ] worked on a novel, reinforced, recycled expanded polystyrene (r-EPS) foam/natural fiber composite obtained via a dissolution method. Coconut husk fiber (coir) and banana stem fiber (BSF) were used as the reinforcement materials in order to enhance the mechanical properties.…”
Section: Overview Of the Papers Included In This Topic Special Issuementioning
confidence: 99%
“…The focus of this analysis was on the identification of feasible solutions to compensate for decreased strength, caused by the reduced density and poor water resistance of foam-formed cellulose composites. An innovative foam/natural fiber composite was successfully developed within the work [ 46 ]. The authors demonstrated an alternative way to produce composites with promising enhanced mechanical properties.…”
Section: Introductionmentioning
confidence: 99%